2019
DOI: 10.1111/cdev.13281
|View full text |Cite
|
Sign up to set email alerts
|

How Early Maternal Language Input Varies by Race and Education and Predicts Later Child Language

Abstract: The maternal language input literature suggests that mothers with more education use a greater quantity and complexity of language with their young children compared to mothers with less education although race and socioeconomic status have been confounded in most studies because of small sample sizes. The current Family Life study included a representative sample of 1,292 children, oversampling for poverty and African American, followed from birth. This study found no race differences within maternal educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…About 70% of the mothers of the total study group had higher education level. Higher maternal socioeconomic status has been linked to higher vocabulary exposure and early vocabulary development in children 4,35 . A higher proportion of mothers with higher education level could possibly reflect some selection bias, with mothers with higher education possibly being more prone to accept participation in the 7‐year assessment, and mothers with lower education being more prone to decline participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 70% of the mothers of the total study group had higher education level. Higher maternal socioeconomic status has been linked to higher vocabulary exposure and early vocabulary development in children 4,35 . A higher proportion of mothers with higher education level could possibly reflect some selection bias, with mothers with higher education possibly being more prone to accept participation in the 7‐year assessment, and mothers with lower education being more prone to decline participation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings imply that milestones in language can be of interest for detecting deficits in intellectual functioning. Maternal education has been found to influence children's language development, through the use of richer and more complex speech directed to the child 4 . Likewise, maternal IQ is a well‐known predictor of children's intellectual functioning 5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, if authors did not provide a classification, SES was determined based on the reported income and education of participants. Given that race/ethnicity and SES are often confounded in studies examining contextually driven word-gaps, we focus only on the potential moderating role of SES, rather than race/ethnicity, in our analyses (Vernon-Feagans et al, 2019). Demographic information including the percentage of participants belonging to minority race/ethnic groups in each sample is provided in Table S3.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Furthermore, there is ample evidence that children learn in contexts in which they receive indirect language exposure (e.g., Akhtar, Jipson, & Callanan, 2001; Akhtar, Tolins, & Tree, 2019). That said, there is considerable historical and current interest in, and emphasis on, this specific metric of the language environment (e.g., Hart & Risley, 1995; Vernon‐Feagans, Bratsch‐Hines, Reynolds, & Willoughby, 2019). As such, syntheses of the association between quantity and quality of direct parental linguistic input and children’s language skills are relevant for our understanding of the role that this aspect of the language environment can play in potentiating children’s language skills.…”
Section: Parental Linguistic Input: Concept Definition and Empirical mentioning
confidence: 99%
“…Families are children's first teachers, and much of children's early language is learned from their parents and other adults who care for them. Mounting research has demonstrated that, on average, children in poverty have different language experiences at home than their more advantaged peers and that these differences in home experiences translate into disparate vocabulary knowledge, which later predicts children's success in learning to read (Morgan et al, 2015;Vernon-Feagans, Bratsch-Hines, Reynolds, & Willoughby, 2019).…”
Section: Home and School Vocabulary Experiencesmentioning
confidence: 99%